Low-energy ion beam bombardment effect on the plant-cell-envelope mimetic membrane for DNA transfer - K. Prakrajang (2018)
This study is a systematic analysis of the mechanisms involved in ion-beam induced DNA transfer, an important application of ion beam biotechnology. Cellulose membranes were used to mimic the plant cell envelope. Ion beams of argon (Ar) or nitrogen (N) at an energy of 25 keV bombarded the cellulose membranes at fluences ranging from 1015to 1016ions/cm2. The damage to the ion-beam-bombarded membranes was characterized using infrared spectroscopy, a micro tensile test and scanning electron microscopy (SEM). Chain scission was the dominant radiation damage type in the membrane. DNA diffusion across the membrane was significantly increased after ion beam bombardment. The increase in DNA transfer is therefore attributed to chain scission, which increases the permeability by increasing the number of pores in the membrane. © 2011 Elsevier B.V. All rights reserved.